1999
DOI: 10.1007/s004330050107
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombin III prevents 60 min warm intestinal ischemia reperfusion injury in rats

Abstract: We investigated the effect of antithrombin III on 60 min warm intestinal ischemia-reperfusion (IR) injury in rats. Sprague-Dawley rats, weighing 220-250 g, were divided into three groups: group 1 sham-operated group (no IR injury, n=8), group 2 ischemic control group (control, Ringer's lactate infused, n=8), group 3 Antithrombin III treated group (250 U/kg before ischemia, n=8). Intestinal ischemia was induced in rats by occluding the superior mesenteric artery for 60 min. Malondialdehyde (MDA) levels, myelope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
3
14

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 25 publications
3
33
3
14
Order By: Relevance
“…This is consistent with previous reports that the peroxidation of cellular membrane lipids and oxidation of cellular proteins, determined by MDA and PCC, respectively, increases by ROS/RNS following I/R injury. [3,8,[30][31][32][33] In addition, we found that the oral supplementation of rats with PA prior to I/R significantly reduced the extent of lipid peroxidation and protein oxidation in the kidneys, indicating decreased cellular injury. Protection of cells might be the consequence of molecular structure of PA, which allows them to accumulate at lipid interfaces [28] and/or to penetrate into membranes.…”
Section: Discussionmentioning
confidence: 66%
“…This is consistent with previous reports that the peroxidation of cellular membrane lipids and oxidation of cellular proteins, determined by MDA and PCC, respectively, increases by ROS/RNS following I/R injury. [3,8,[30][31][32][33] In addition, we found that the oral supplementation of rats with PA prior to I/R significantly reduced the extent of lipid peroxidation and protein oxidation in the kidneys, indicating decreased cellular injury. Protection of cells might be the consequence of molecular structure of PA, which allows them to accumulate at lipid interfaces [28] and/or to penetrate into membranes.…”
Section: Discussionmentioning
confidence: 66%
“…37 Myeloperoxidase activity in intestinal tissue increased 3-fold after 60-minute intestinal ischemia and 8-to 9-fold after 60-minute reperfusion. 38 Ozden and associates 27 showed that mucosal myeloperoxidase activity was increased in the control group, confirming postreperfusion neutrophil infiltration compared with that shown in the sham group. Reduced myeloperoxidase activity in the antithrombin groups showed that antithrombin inhibited polymorphonuclear infiltration in the reperfused intestine.…”
Section: Discussionmentioning
confidence: 70%
“…In addition, myeloperoxidase as an index of polymorphonuclear accumulation was significantly less in the IPC groups and especially in the groups treated with AT, in agreement with similar studies. 27 Tumor necrosis factor α is the central component of the proinflammatory cytokine cascade in liver IRI and is a crucial effecter of remote organ damage after hepatic IRI. 28,29 It has been reported that TNF-α elevation was responsible for pulmonary damage after hepatic IRI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using an Albino rat model, Herek infused the animals with phAT with 250 U/kg phAT prior to infecting them and creating a burned surface; phAT-treated rats had reduced intestinal villi degeneration and decreased bacterial translocation to mesenteric lymph nodes, spleen and liver compared to sham and control rat (P < 0.02) [62] . This study followed the work of Ozden et al [63] who showed that an infusion of phAT prevented an ischemic reperfusion injury in the rat.…”
Section: Bacterial Translocationmentioning
confidence: 99%